New families and subfamilies of amphipod crustaceans - Lowry, J. K. (Zootaxa, 2006)
Cleonardopsis K.H. Barnard, 1916, has been incorrectly placed in the Eusiridae. Based on mouthpart morphology, body carination and the shape of the gnathopods it is reassigned to the Amathillopsidae in the new subfamily Cleonardopsinae. Cleonardopsinae is cosmopolitan in the deep sea. Parepimeria Chevreux, 1911, has been incorrectly placed in the Epimeriidae. Coleman & Barnard (1991) suggested that it be moved to the Pleustidae. Bousfield & Hendrycks (1994) rejected this suggestion. It is excluded from the Pleustidae because of the progressively larger and ventrally acute coxae 1 to 4, simple first and second gnathopods and carinate urosomites. Parepimeria appears to be a sister taxon of Amathillopsis Heller, 1875, and forms the basis of a new monotypic subfamily, Parepimeriinae, within the Amathillopsidae. Parepimeriinae appears to be a Southern Ocean endemic. Miramarassa Ortiz, Lalana & Lio (1999) was originally placed in the Aristiidae mainly because it has an elongate ischium on gnathopod 2. It is excluded from the aristiids and the lysianassoids, because of the slender antenna 1 which is characteristically non-lysianassoid, the mandibular incisor which is curved and serrate and the lacinia mobilis which occurs on both mandibles. A monotypic family, Miramarassidae, is established which may have affinities with iphimedioid taxa. Miramarassidae is currently known only from Cuba. Regalia K.H. Barnard (1930) has generally been considered as a calliopiid amphipod, although some workers have discussed its similarity to the Pleustidae. A fresh evaluation of the genus has shown that characters not considered by earlier workers, such as a callynophore on antenna 1, brush setae on antenna 2 and a straight, minutely serrate incisor on the mandible, indicate that Regalia cannot be a calliopiid or a pleustid. Regalia appears to be most similar to members of the Pardaliscidae, but a number of characters such as the lack of an accessory flagellum, the presence of a left and right lacinia mobilis, a well developed molar and lateral ridging on the pleosome exclude it from this family. Consequently Regaliidae is established as a new monotypic family for Regalia, with an Indo-West Pacific distribution. Sancho Stebbing, 1897, has most recently been placed in the             Eusiridae (sensu lato), but might be more suited to the Calliopiidae (sensu stricto) because of its entire telson. Unlike eusirids or calliopiids, species of Sancho have a non-recessed head and a dorsoventrally flattened urosome. Sanchoidae is established as a new monotypic family for Sancho, currently known from shallow water in south-eastern Australia.